Robustness of PWA Control Based on A Coupled Vertex Sensitivity Analysis. Issue 16 (2022) - Yang, Songlin; Olaru, Sorin; Rodriguez-Ayerbe, Pedro; Dorea, Carlos E.T.
Abstract: Under the vertex representation for the state partitions, this paper studies the robustness of PWA control for constrained discrete-time linear systems. In particular, the aim is to evaluate the impact of uncertainty in the representation of state-space partition. Practically, the notion of coupled vertex sensitivity (CVS) is defined to inscribe the joint uncertainty in the vertex positioning. This novel concept reduces the computational complexity and the conservativeness of the construction compared to the use of independent vertex perturbation through the iterative procedure using the existing results. A numerical example illustrated the effectiveness of our work.